Beta-blocker use in patients with heart failure with preserved ejection fraction and sinus rhythm - Formiga, Francesc; Chivite, David; Nuñez, Julio; Moreno García, Ma Carmen; Manzano, Luis; Arévalo-Lorido, José Carlos; Cerqueiro, Jose Manuel; García Campos, Álvaro; Trullàs, Joan Carles; Montero-Pérez-Barquero, Manuel (Revista portuguesa de cardiologia, 2022)
Beta-adrenergic receptor blockers (beta-blockers) are frequently used for patients with heart failure (HF) with preserved ejection fraction (HFpEF), although evidence-based recommendations for this indication are still lacking. Our goal was to assess which clinical factors are associated with the prescription of beta-blockers in patients discharged after an episode of HFpEF decompensation, and the clinical outcomes of these patients. We assessed 1078 patients with HFpEF and in sinus rhythm who had experienced an acute HF episode to explore whether prescription of beta-blockers on discharge was associated with one-year all-cause mortality or the composite endpoint of one-year all-cause death or HF readmission. We also examined the clinical factors associated with beta-blocker discharge prescription for such patients. At discharge, 531 (49.3%) patients were on beta-blocker therapy. Patients on beta-blockers more often had a prior diagnosis of hypertension and more comorbidity (including ischemic heart disease) and a better functional status, but less often a prior diagnosis of chronic obstructive pulmonary disease. These patients had a lower heart rate on admission and more often used angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, angiotensin receptor-neprilysin inhibitors and loop diuretics. One year after the index admission, 161 patients (15%) had died and 314 (29%) had experienced the composite endpoint. After multivariate adjustment, beta-blocker prescription was not associated with either all-cause mortality (HR=0.83 [95% CI 0.61-1.13]; p=0.236) or the composite endpoint (HR=0.98 [95% CI 0.79-1.23]; p=0.882). In patients with HFpEF in sinus rhythm, beta-blocker use was not related to one-year mortality or mortality plus HF readmission. Os bloqueadores dos recetores β-adrenérgicos (bloqueadores-β) são frequentemente utilizados nos doentes com insuficiência cardíaca (IC) com fração de ejeção preservada (IC-FEp), embora ainda escasseiem as recomendações baseadas na evidência para essa indicação. O nosso objetivo foi avaliar que fatores clínicos estão associados à prescrição de β-bloqueadores em doentes com alta após um episódio de descompensação por IC-FEp e os outcomes destes doentes. Avaliámos 1078 doentes com IC-FEp em ritmo sinusal após um episódio de IC aguda para avaliar se a utilização de bloqueadores-β no momento da alta se associou à mortalidade global ao fim de um ano ou ao endpoint composto de mortalidade global ao fim de um ano ou reinternamento por IC. No momento da alta, 531 (49,3%) doentes estavam medicados com bloqueadores-β. Estes doentes apresentaram mais frequentemente um diagnóstico prévio de hipertensão e mais comorbilidades (incluindo doença cardíaca isquémica) e um melhor status funcional, mas com menor frequência um diagnóstico prévio de doença pulmonar obstrutiva crónica. Apresentaram também uma frequência cardíaca mais baixa no momento do internamento e foram tratados mais frequentemente com inibidores da enzima de conversão da angiotensina, bloqueadores dos recetores de angiotensina, inibidores dos recetores de angiotensina-neprilisina e diuréticos de ansa. Um ano após a admissão-índice, 161 doentes (15%) tinham morrido e 314 (29%) tinham atingido o objetivo composto. Após análise multivariada, a indicação para bloqueadores-β não se associou nem ao endpoint primário s [HR=0,83 (CI 95%: 0,61-1,13); p=0,236] nem ao composto [HR=0,98 (CI 95%: 0,79-1,23); p=0,882]. Em doentes com IC-FEp em ritmo sinusal, a utilização de bloqueadores-β não se associou à redução da mortalidade global a um ano nem à redução de mortalidade global e reinternamento por IC.